2016
DOI: 10.1161/hypertensionaha.116.07461
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Aberrant Blood Pressure and Sympathetic Regulation in Diet-Induced Obesity

Abstract: O besity, a state of excessive adipose tissue accumulation, has reached epidemic proportions worldwide, and this increasing global prevalence constitutes a major public health challenge. Obesity is one of the main causes of hypertension. Both human and animal studies present a strong link between bodyweight gain and greater blood pressure.1 Importantly, obesity-related hypertension is caused by an interaction of humoral and neural mechanisms, 2,3 and inappropriate increases in sympathetic tone are thought to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
(78 reference statements)
3
22
0
Order By: Relevance
“…More specifically, it has been shown that nonspecific blockade of the ArcN and PVN [76,77] both decrease SNA in DIO male rats. While these results may reflect the actions of several sympathoexcitatory factors, other reports indicate that, in obese animals, select blockade of leptin receptors in the ArcN [36], VMH [78], or DMH [69] decreases SNA and/or MAP. Nevertheless, two studies were unable to confirm a role for the DMH in obesity-induced sympathoexcitation [77,78].…”
Section: Leptinmentioning
confidence: 71%
“…More specifically, it has been shown that nonspecific blockade of the ArcN and PVN [76,77] both decrease SNA in DIO male rats. While these results may reflect the actions of several sympathoexcitatory factors, other reports indicate that, in obese animals, select blockade of leptin receptors in the ArcN [36], VMH [78], or DMH [69] decreases SNA and/or MAP. Nevertheless, two studies were unable to confirm a role for the DMH in obesity-induced sympathoexcitation [77,78].…”
Section: Leptinmentioning
confidence: 71%
“…Other investigators have shown no effect on baseline blood pressure of leptin receptor knockdown in the PVN, but that this prevented an increase in blood pressure after direct injection of leptin into the PVN [48]. On the other hand, injection of a leptin receptor antagonist into the VMH but not the DMH reversed the increases in blood pressure, heart rate, and renal SNA in high fat fed rabbits [49]. Conversely, reactivation of leptin receptors only in the DMH increased blood pressure in high fat fed mice while DMH-restricted administration of a leptin receptor antagonist decreased blood pressure in mice fed a high fat diet [28].…”
Section: Neuronal Substrates Of Leptin Actionmentioning
confidence: 99%
“…Although obese people are resistant to leptin's actions to suppress food intake, the resistance is selective; the adipokine continues to stimulate systems that augment energy expenditures . Leptin can contribute to activation of the sympathetic nervous system and renin‐angiotensin system in obesity and to both sodium retention and cardiac fibrosis . Leptin is not merely a marker of obesity; it exerts important effects, as is evidenced by the fact that the neurohormonal activation and coronary vascular abnormalities in diet‐induced obesity are blocked by synthetic leptin antagonists …”
Section: Effects Of Leptin On Heart Failure With a Preserved Ejectionmentioning
confidence: 99%